Replication of bacterial plasmids in the nucleus of the red alga Porphyridium purpureum - Zhichao Li (Nature Portfolio, 2018)
Genetic tools for research on red algae (rhodophytes) are lacking. Here, Li and Bock present an efficient genetic transformation system for a model rhodophyte, and show that the transgenic DNA can be maintained as an extrachromosomal multi-copy plasmid in the algal nucleus.